ANALISIS VARIABILITAS SPASIAL KETEBALAN DAN NILAI KALORI PADA PERSEBARAN CADANGAN BATUBARA MENGGUNAKAN METODE ORDINARY KRIGING (STUDI KASUS: BLOK SELATAN PIT 1B - LAMIN MINE OPERATION PT MEGA ALAM SEJAHTERA, KAB. BERAU, PROV. KALIMANTAN TIMUR ) - Ajatasatru, Anshar
Coal thickness and calorific value are two variables in coal seam which have characteristic of spatial continuity that may vary in accordance of geological depositional influence. This research aims to obtain the accuracy and precision of spatial variability analysis from thickness and calorific value of coal using Ordinary Kriging method and later it is to be used as a reference to determine the economically effective mine development strategy. Dissemination of coal thickness and calorific value from seam AA1 and seam A in longterm area of South Block Pit 1B is assumed to be valid, stationer, and no outliers is indicated. Furthermore, structural analysis using geometric anisotropy variogram is conducted with lag size corresponds to drill holes average spacing of 50 m and number of lags is 16. Then, Ordinary Kriging interpolation is carried out by calculating the weight matrix vector in order to acquire kriging variance. Degree of accuracy from estimation result can be seen from RMSE of interpolated values from both coal thickness and calorific value that is supported with cross-validation process to assess unbiasedness level and degree of precison from estimated standard deviation. From estimation result, variable of seam AA1 thickness with RMSE value 0,19 tends to be more homogeneous instead of seam A thickness with RMSE value 0,25. Whereas, calorific value of seam AA1 with RMSE 34,61 tends to be more heterogeneous instead of calorific value from seam A with RMSE 33,77. Cross-validation result reveals that overall of interpolated values is regarded unbiased in accordance to its estimated standard deviation from coal thickness and calorific value of both seam hence, those estimated coal variables indicate low spatial variability and high spatial continuity. Therefore, the estimated result is then to be used to bear the ratio of overburden-seam information in establishing optimum mine development strategy thus, the mining operational cost can be degraded and upgrade the effectiveness of mine development.